Exploring the potential of ammonia as a fuel: Advances in combustion understanding and large-scale furnace applications - Eckart, Sven; Salzano, Ernesto; Richter, Andreas; Alnajideen, Mohammad; Valera-Medina, Agustin; Shrestha, Krishna Prasad; Yasiry, Ahmed; Wang, Jinhua; Bauer, Florian; Yu, Chunkan; Krause, Hartmut; Pio, Gianmaria (Fuel, 2025)
From an environmental standpoint, carbon-free energy carriers such as ammonia and hydrogen are essential for future energy systems. However, their high-temperature chemical behavior remains insufficiently understood, posing challenges for the development and optimization of advanced combustion technologies. Ammonia, in particular, is globally available and cost-effective, especially for energy-intensive industries. The addition of ammonia or hydrogen to methane significantly reduces the accuracy of existing predictive models. Therefore, validated and detailed data are urgently needed to enable reliable design and performance predictions. This review highlights the compatibility of ammonia with existing combustion infrastructure, facilitating a smoother transition to more sustainable heating methods without the need for entirely new systems. Applications in high-temperature heating processes, such as metal processing, ceramics and glass production, and power generation, are of particular interest. This review focuses on the systematic assessment of alternative fuel mixtures comprising ammonia and hydrogen, as well as natural gas, with particular consideration of existing safety-related parameters and combustion characteristics. Fundamental quantities such as the laminar burning velocity are discussed in the context of their relevance for fuel mixtures and their scalability toward turbulent flame propagation, which is of critical importance for industrial burner and reactor design. The influence of fuel composition on ignition limits is examined, as these are essential parameters for safety margin definitions and operational boundary conditions. Furthermore, flame stability in mixed-fuel systems is addressed to evaluate the practical feasibility and robustness of combustion under varying process conditions. A detailed overview of current diagnostic and analysis methods follows, encompassing both pollutant measurement techniques and the detection of key radical species. These diagnostics form the experimental basis for reaction kinetics modeling and mechanism validation. Given the importance of emission formation in combustion systems, a dedicated subsection summarizes major emission trends, even though a comprehensive treatment would exceed the scope of this review. Thermal radiation effects, which are highly relevant for heat transfer and system efficiency in large-scale applications, are then reviewed. In parallel, current developments in numerical simulation approaches for industrial-scale combustion systems are presented, including aspects of model accuracy, boundary conditions, and computational efficiency. The review also incorporates insights from materials engineering, particularly regarding high-temperature material performance, corrosion resistance, and compatibility with combustion products. Based on these interdisciplinary findings, operational strategies for high-temperature furnaces are outlined, and selected industrial reference systems are briefly presented. This integrated approach aims to support the design, optimization, and safe operation of next-generation combustion technologies utilizing carbon-free or low-carbon fuels.
CRIS-Team Scopus Importer:2025-10-16